Developing supplementary speaking material for flight attendant and ground staff program of Dirgantara vocational high school - Istiqomah, Endah Kunti (Journal of English Language and Pedagogy, 2024)
The purposes of this study are (1)  to know weaknesses of the textbook in English for Airlines used by the students of Dirgantara vocational high 11th grades school majoring flight attendant and ground staff, (2) to develop the supplementary speaking material for flight attendant and ground staff program of Dirgantara Vocational High School (3) reveal the efficacy of the developed suppelementary material to English for Airlines textbook for the students of Dirgantara Vocational High School 11th grades majoring as a flight attendant and ground staff. This research belongs to Educational Research and Development (R&D) using simplified step of Borg and Gall’s model. The steps are as follows. (1) Research and information collecting was conducted by performing document analysis, class observation and interview, (2) Planning and drafting was conducting by drafting the textbook for the students. In this step, the researcher designed the syllabus, material and then the textbook, (3) Draft Revision by Expert, (4) Field testing was conducted in Ngurahrai class of Dirgantara Vocational High School, (5) Revision and the last (6) Final product. The findings show that (1) the weaknesess of the textbook is that the textbook did not provide the appropriate material which students’ need, (2) In English for Airlines textbook; pre-activicty stated in the starter, whilst activity stated in the activity 1-5 and post activity stated in the activity 6-7 were appropriate to the students in the classroom, (3) the efficacy of speaking material help the students to achieve their specific purpose of their program, improve the vocabularies, and enhance their speaking skill. Furthermore, the speaking material as the product of this study provide learning resources to the students and teacher.